2008
DOI: 10.1111/j.1468-1293.2008.00628.x
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance profiles for the HIV integrase gene in patients failing raltegravir salvage therapy*

Abstract: ObjectivesRecent data showed the selection of mutations in the integrase gene, mainly involving position 148 or 155, in patients displaying virological failure (VF) on raltegravir (RAL) therapy. Here, we describe the development of RAL resistance, in both plasmatic and cellular compartments, in three heavily pretreated HIV-infected patients failing RAL-containing regimens. MethodsThree of 17 patients receiving RAL displayed VF. The entire integrase gene, isolated from plasma and peripheral blood mononuclear ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
76
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 14 publications
4
76
0
Order By: Relevance
“…In addition, the secondary mutation E92Q preferentially resides on virus clones bearing the N155H mutation while G140S(A) is selected by viruses bearing mutations at position 148. In this study population (a subset of virologic failures from BENCHMRK I and II), the identification of E92Q in the absence of N155H was rare (1/69 RAL failures), consistent with other reports (4,20). We also observed primary IN mutations at position 143, albeit at a low frequency (4/69 or 6%) compared to the selection of mutations at position 155 only (31/69 or 45%) and 148 only (R, H, K; 20/69 or 29%) at the time of the first virologic failure.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, the secondary mutation E92Q preferentially resides on virus clones bearing the N155H mutation while G140S(A) is selected by viruses bearing mutations at position 148. In this study population (a subset of virologic failures from BENCHMRK I and II), the identification of E92Q in the absence of N155H was rare (1/69 RAL failures), consistent with other reports (4,20). We also observed primary IN mutations at position 143, albeit at a low frequency (4/69 or 6%) compared to the selection of mutations at position 155 only (31/69 or 45%) and 148 only (R, H, K; 20/69 or 29%) at the time of the first virologic failure.…”
Section: Discussionsupporting
confidence: 74%
“…Recently, several reports have described the evolution of IN resistance mutations under continued RAL pressure in the absence of complete viral suppression (4,6,21 . Additional case studies have also documented evolution from N155N/H to Q148H (4) or N155H to Y143R in subjects with incomplete viral suppression (6).…”
Section: Discussionmentioning
confidence: 99%
“…This may result in a perturbed infection of T-lymphocytes and subsequent altered apoptosis. In fact, it is already known that M/M can recruit lymphocytes and trigger their death, through several events, mediated by viral proteins (such as nef and gp120), or by chemokines and other factors produced during HIV-1 infection (Badley et al, 1997;Charpentier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in RAL phase II and III clinical trials, investigators noted that N155H variants detected at the first fail-ure time point were frequently replaced by Q148H, K, or R variants at later time points in the presence of ongoing RAL exposure (22,23). Other groups have also reported shifts from N155H to Q148H (3,21,24), as well as shifts from N155H to Y143R (5).…”
mentioning
confidence: 99%
“…For the most part, RAL-and EVG-resistant variants remain susceptible to DLG (S/GSK1349572), which, in vitro, selects for a distinct mutation profile that includes L101I, T124A, and S153F or Y (16). A notable exception may be viruses containing mutations at position 148, which in vitro can exhibit reduced susceptibility to DLG when they also contain specific secondary mutations (16) Studies evaluating sequential virus samples have reported shifts in primary IN inhibitor resistance mutation patterns in subjects remaining on RAL following virologic treatment failure (3,5,9,20,22,23). Specifically, in RAL phase II and III clinical trials, investigators noted that N155H variants detected at the first fail-ure time point were frequently replaced by Q148H, K, or R variants at later time points in the presence of ongoing RAL exposure (22,23).…”
mentioning
confidence: 99%